2011
DOI: 10.1002/ijc.26218
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐30a inhibits epithelial‐to‐mesenchymal transition by targeting Snai1 and is downregulated in non‐small cell lung cancer

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs which regulate gene expression by base-pairing to the 3 0 -UTR of the target mRNA. Recently, miRNAs have been shown to regulate cancer metastasis, however, central molecular mechanisms of this ability still need to be investigated. Epithelial to mesenchymal transition (EMT), which is characterized especially by repression of E-cadherin expression and increased cell motility, is an essential component of cancer metastasis and progression. In the present study, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
190
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(236 citation statements)
references
References 37 publications
44
190
1
1
Order By: Relevance
“…[37][38][39][40][41] For e.g., let-7, miR-30a, miR-125a-5p, miR-126, miR-183, miR-200, miR-21, miR-221, miR-222, and miR-328 have important roles in EMT, invasion, and metastasis of lung cancer. [42][43][44][45][46][47] In this study, we found that enforced expression of miR-19 (i.e., miR-19a and miR-19b-1) in lung cancer cells A549 and HCC827 cells triggered EMT, as shown by mesenchymal-like morphological changes, downregulation of epithelial proteins (e.g., E-cadherin, ZO-1, and α-catenin), upregulation of mesenchymal proteins (e.g., vimentin, FN1, N-cadherin, or snail1), formation of stress fibers, reduced cell adhesion, and enhanced cell migration and invasion. In addition, DNA microarray results also highlighted the expression of genes involved in EMT, migration, and metastasis in miR-19-expressing A549 cells.…”
Section: Discussionsupporting
confidence: 42%
“…[37][38][39][40][41] For e.g., let-7, miR-30a, miR-125a-5p, miR-126, miR-183, miR-200, miR-21, miR-221, miR-222, and miR-328 have important roles in EMT, invasion, and metastasis of lung cancer. [42][43][44][45][46][47] In this study, we found that enforced expression of miR-19 (i.e., miR-19a and miR-19b-1) in lung cancer cells A549 and HCC827 cells triggered EMT, as shown by mesenchymal-like morphological changes, downregulation of epithelial proteins (e.g., E-cadherin, ZO-1, and α-catenin), upregulation of mesenchymal proteins (e.g., vimentin, FN1, N-cadherin, or snail1), formation of stress fibers, reduced cell adhesion, and enhanced cell migration and invasion. In addition, DNA microarray results also highlighted the expression of genes involved in EMT, migration, and metastasis in miR-19-expressing A549 cells.…”
Section: Discussionsupporting
confidence: 42%
“…The majority of previous studies have shown that miR-30 family members act as tumor suppressors in various types of cancer (2)(3)(4). In addition, miR-30 family members are frequently found to be downregulated in these types of tumor tissue.…”
Section: Introductionsupporting
confidence: 44%
“…In other investigations, miR-30b and miR-30c were found to inhibit sarcoma viral oncogene homolog, which affected gefitinib-induced apoptosis and the EMT of NSCLC cells (14). miR-30a was also found to be negatively associated with the expression of N-cadherin, a mesenchymal marker (2), and miR-30d was demonstrated to inhibit tumor growth and invasion in NSCLC (15). However, the possible role of miR-30a in lung cancer remains to be elucidated.…”
Section: Introductionsupporting
confidence: 42%
See 1 more Smart Citation
“…Different tumor types and tumors at various differentiation stages may exhibit unique miRNA profiles (15). In nonsmall cell lung cancer (NSCLC) cells, miRNA (miR)-494, miR-30a, miR-193b, miR-101, miR-7, and miR-206 have been reported as tumor inhibitors (16)(17)(18)(19)(20)(21), whereas miR-212 is believed to promote carcinogenesis in vitro (22). In patients with NSCLC, high miR-155 and low let-7a-2 expression in tumor tissue have been reported to correlate with poor survival (23).…”
Section: Introductionsupporting
confidence: 46%